2022
DOI: 10.1002/advs.202104671
|View full text |Cite
|
Sign up to set email alerts
|

A “Valve‐Closing” Starvation Strategy for Amplification of Tumor‐Specific Chemotherapy

Abstract: Starvation‐dependent differential stress sensitization effect between normal and tumor cells provides a potentially promising strategy to amplify chemotherapy effects and reduce side effects. However, the conventional starvation approaches such as glucose oxidase (Gox)‐induced glucose depletion and nanomedicine‐enabled vascular embolism usually suffer from aggravated tumor hypoxia, systemic toxicity, and unpredictable metabolic syndrome. Herein, a novel “valve‐closing” starvation strategy is developed to ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Genistein, a natural compound extracted from soybean, is the member of the soybean isoflavone family with the most extensive biological activities and antitumor effects [ 8 ]. Previous reports have shown that genistein has the functions of protecting the cardiovascular system, regulating blood glucose, delaying neurological decline and antitumor [ 9 , 10 , 11 , 12 ]. In addition, recent studies on genistein have confirmed that it possesses the ability to inhibit the proliferation, invasion and metastasis of a variety of cancers, including HCC, renal cancer and breast cancer [ 8 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genistein, a natural compound extracted from soybean, is the member of the soybean isoflavone family with the most extensive biological activities and antitumor effects [ 8 ]. Previous reports have shown that genistein has the functions of protecting the cardiovascular system, regulating blood glucose, delaying neurological decline and antitumor [ 9 , 10 , 11 , 12 ]. In addition, recent studies on genistein have confirmed that it possesses the ability to inhibit the proliferation, invasion and metastasis of a variety of cancers, including HCC, renal cancer and breast cancer [ 8 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a glucose analogue, 2-deoxy- d -glucose (2-DG) has been extensively studied as an antiglycolytic agent to inhibit the production of ATP and lactate. However, tumor cells can massively convey glucose by the overexpressed glucose transporter 1 (GLUT1), seriously weakening the inhibition effect of 2-DG to glycolysis. , BAY-876, an emerging highly selective and potent inhibitor of GLUT1, has shown satisfactory behavior to block glucose uptake of tumor cells. , Hence, combining 2-DG with BAY-876 appears to be an ideal strategy to cut off the energy and nutrition supply for tumor cells. Even so, cunning tumor cells can activate a so-called autophagy mechanism to “eat” and “digest” their damaged organelles and misfolded proteins to maintain cell homeostasis. It is reported that chloroquine (CQ) can alkalize the lysosome and inhibit their fusion with autophagosomes, thus blocking the autophagy process .…”
mentioning
confidence: 99%
“…transporter 1 (GLUT1), seriously weakening the inhibition effect of 2-DG to glycolysis. 33,34 BAY-876, an emerging highly selective and potent inhibitor of GLUT1, has shown satisfactory behavior to block glucose uptake of tumor cells. 35,36 Hence, combining 2-DG with BAY-876 appears to be an ideal strategy to cut off the energy and nutrition supply for tumor cells.…”
mentioning
confidence: 99%
“…In traditional cancer therapy, chemotherapy is an effective and indispensable therapeutic approach. [1][2][3] However, conventional chemotherapeutic drugs are still confronted with limitations, such as poor water-solubility, severe toxicity and side effects, and non-fluorescent indication. 2 Besides, as chemotherapy advances, the over-activated DNA damage repair system within tumor cells exacerbates genomic instability, resulting in enhanced drug resistance to DNA damage agents, and it ultimately may promote the invasion and metastasis of tumor cells.…”
mentioning
confidence: 99%
“…[1][2][3] However, conventional chemotherapeutic drugs are still confronted with limitations, such as poor water-solubility, severe toxicity and side effects, and non-fluorescent indication. 2 Besides, as chemotherapy advances, the over-activated DNA damage repair system within tumor cells exacerbates genomic instability, resulting in enhanced drug resistance to DNA damage agents, and it ultimately may promote the invasion and metastasis of tumor cells. 1 Prodrugs modified by peculiar chemical bonding with enhanced water solubility, target ability, and stimuli-responsive ability have been provided to solve these problems.…”
mentioning
confidence: 99%